Timing of mTOR activation affects tuberous sclerosis complex neuropathology in mouse models - Laura Magri; Manuela Cominelli; Marco Cambiaghi; Marco Cursi; Letizia Leocani; Fabio Minicucci; Pietro Luigi Poliani; Rossella Galli (The Company of Biologists, 2013)
SUMMARY Tuberous sclerosis complex (TSC) is a dominantly inherited disease with high penetrance and morbidity, and is caused by mutations in either of two genes, TSC1 or TSC2. Most affected individuals display severe neurological manifestations - such as intractable epilepsy, mental retardation and autism - that are intimately associated with peculiar CNS lesions known as cortical tubers (CTs). The existence of a significant genotype-phenotype correlation in individuals bearing mutations in either TSC1 or TSC2 is highly controversial. Similar to observations in humans, mouse modeling has suggested that a more severe phenotype is associated with mutation in Tsc2 rather than in Tsc1. However, in these mutant mice, deletion of either gene was achieved in differentiated astrocytes. Here, we report that loss of Tsc1 expression in undifferentiated radial glia cells (RGCs) early during development yields the same phenotype detected upon deletion of Tsc2 in the same cells. Indeed, the same aberrations in cortical cytoarchitecture, hippocampal disturbances and spontaneous epilepsy that have been detected in RGC-targeted Tsc2 mutants were observed in RGC-targeted Tsc1 mutant mice. Remarkably, thorough characterization of RGC-targeted Tsc1 mutants also highlighted subventricular zone (SVZ) disturbances as well as STAT3-dependent and -independent developmental-stage-specific defects in the differentiation potential of ex-vivo-derived embryonic and postnatal neural stem cells (NSCs). As such, deletion of either Tsc1 or Tsc2 induces mostly overlapping phenotypic neuropathological features when performed early during neurogenesis, thus suggesting that the timing of mTOR activation is a key event in proper neural development.